Shariah Governance Practices of Malaysian Islamic Banks in the Light of Shariah Compliance - Rosnia Masruki; Mustafa Mohd Hanefah; Dhar, Bablu Kumar (Penerbit Univ Kebangsaan Malaysia, 2024)
Non-Indexed Publication